If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A + 5b + -2a + 9b = 0 Reorder the terms: A + -2a + 5b + 9b = 0 Combine like terms: 5b + 9b = 14b A + -2a + 14b = 0 Solving A + -2a + 14b = 0 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '2a' to each side of the equation. A + -2a + 2a + 14b = 0 + 2a Combine like terms: -2a + 2a = 0 A + 0 + 14b = 0 + 2a A + 14b = 0 + 2a Remove the zero: A + 14b = 2a Add '-14b' to each side of the equation. A + 14b + -14b = 2a + -14b Combine like terms: 14b + -14b = 0 A + 0 = 2a + -14b A = 2a + -14b Simplifying A = 2a + -14b
| X=-10.5-1.5(0) | | 5.6(3+4x)-5.8=11 | | X=-10.5-1.5y | | 3n+1-2n+8= | | (7x-1)/(5x-9) | | 12a^2-5ab-2b^2= | | cd-ab= | | 5+3(3-2x)=5x+3(3x-2) | | 5x+2=32+8x | | 2/3(4y-4)/3≥-4 | | 4x-5=16+11c | | 9x+7=27-5x | | 2x^2-6x/7x-21 | | -15-5-(-18)= | | C=3.14(40) | | 5x^3=24 | | 2(x+1)+2x=x+5 | | q(x)=2x^2+12x-11 | | 64x^6=1 | | 7(2y+5)+(-26y)= | | (3x+5)+(2x+1)=5(x-1)+9 | | 9x-9=5x+7 | | 14+(-3)+5+8+(-2)= | | (1+t)sqrt(k)+4k=1 | | 6-(2y-6)=9-3y | | (1+g)sqrt(k)+4k=1 | | 4=3x+5(x+4) | | a-10b/8a-5a-11b/8a | | 5+6r-3=7r+8-3r | | 3(y-7)-8y=4 | | 7y+4=8y | | 0.02/0.7 |